A new Occidozyga from Sarawak, Malaysian Borneo (Anura: Dicroglossidae) - Matsui, Masafumi; Nishikawa, Kanto; Eto, Koshiro; Hamidy, Amir; Hossman, Yazid; Fukuyama, Ibuki (Zootaxa, 2021)
We found a uniquely colored dicroglossid frog of the genus Occidozyga from western Sarawak, East Malaysia. It is divergent from other congeners in morphology and mtDNA sequences. In a molecular phylogeny, this species is the sister lineage to the continental species O. lima and O. martensii with weak support. The species is small with SVL 16–18 mm in males and 18–19 mm in females, without dorsolateral fold but with transverse wrinkles on dorsum, tips of fingers lacking disks but of toes with disks, only first and second toes webbed to disks, and orange-brown dorsum with dark brown band. We thus describe it as a new species.